Effects of Electroacupuncture at Governor Vessel Acupoints on Neurotrophin-3 in Rats with Experimental Spinal Cord Injury - Yu-ping Mo; Hai-jiang Yao; Wei Lv; Liang-yu Song; Hong-tao Song; Xiao-chen Yuan; Ying-qiu Mao; Quan-kai Jing; Su-hua Shi; Zhi-gang Li (Neural Plasticity)
In an effort to explore new, noninvasive treatment options for spinal cord injuries (SCI), this study investigated the effects of electroacupuncture (EA) for SCI rat models. SCI was induced by a modified Allen’s weight-drop method. We investigated the response of EA at Dazhui (GV 14) and Mingmen (GV 4) acupoints to understand the effects and mechanisms of EA in neuroprotection and neuronal function recovery after SCI. BBB testing was used to detect motor function of rats’ hind limbs among groups, and EA was shown to promote the recovery of SCI rats’ motor function. Nissl staining showed a restored neural morphology and an increase in the quantity of neurons after EA. Also, the antiapoptosis role was exposed by TUNEL staining. Western blotting analysis was used to determine the protein expression of neurotrophin-3 (NT-3) in spinal cord tissue. Compared to the sham group, the expression levels of NT-3 were significantly decreased and EA was shown to upregulate the expression of NT-3. The present study suggests that the role of EA in neuroprotection and dorsal neuronal function recovery after SCI in rats, especially EA stimulation at GV 14 and GV 4, can greatly promote neuronal function recovery, which may result from upregulating the expression of NT-3.